An analysis of the solar service provider industry in the Western Cape, South Africa - Votteler, Roman; Hough, Johan; Venter, Chanel (Journal of Energy in Southern Africa, 2014)
Scientists agree that rising electricity usage of the rapidly growing human race to improve its standard of living is negatively affecting the environment. To create a sustainable environment for future generations, renewable and environmentally friendly resources have to be exchanged for the present finite resources. In South Africa, coal plants are responsible for more than 90% of electricity production. This means that action has to be taken now to start a process of change to sustainable electricity resources.This paper focuses on the South African solar industry. Due to the high sun radiation levels, solar technology is one of the renewable energy sources with the greatest potential. The industry is in its infancy, characterised by accelerated growth expectancy and fuelled by factors such as government subsidies, the fluctuations of fossil fuel prices and the increasing focus on economical long-term sustainability. The expected growth necessitates a focus on the market positioning of solar service providers in the Western Cape, with the aim of taking full advantage of the opportunities associated with this industry.The main objective is to determine the current structure of the solar service provider value chain and subsequently areas of improvement to increase growth, stakeholder satisfaction and sustainability. A literature review was conducted to address the research objective, relevant approaches and the broader electricity industry. Porter’s Value Chain approach was used as a foundation for the adaptation to the solar service provider value chain. Porter’s Five Forces model was also used as a secondary approach, which analysed the competitive environment of the solar service provider industry in the Western Cape. The methodology entailed a qualitative research approach in the form of semi-structured interviews. All respondents were general managers or owners of a solar service provider, who were interviewed face to face. The research focused on the entire population of solar service providers in the Western Cape. Seventy-seven different service providers were targeted, of which 18 were interviewed. The interviews were transcribed and analysed using content and frequency analysis. To guarantee reliability, a pilot study was conducted to ensure that the respondents understood the questionnaire. The findings show that customer service is the foremost value driver for solar service providers. This entails the actual installation of the product as well as the people skills of the installation team. As most customers only have to be served once due to the long life span of the products, marketing also plays an obvious role in attracting new customers. The most important outcome of this paper is the determination and a better understanding of the solar service provider value chain in South Africa. The recommendations, especially with regard to marketing and service elements, could improve the performance of solar service providers. The consequence could be an increase in stakeholder satisfaction and an enhanced usage of solar energy in South Africa. Future research should focus on customers to reveal preferences and opportunities for marketing approaches.